HUBUNGAN EFIKASI DIRI DENGAN NILAI OBJECTIVE STRUCTURED CLINICAL EXAMINATION (OSCE) PADA MAHASISWA TAHUN KETIGA FAKULTAS KEDOKTERAN UNIVERSITAS RIAU - Wan Risa Mailina; Zulharman "; Enikarmila Asni (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2015)
ABSTRACTBandura explains that self-efficacy is a person’s belief about ability to perform a task or action to achieve a particular result. Students with high self-efficacy will be able to deal with the OSCE successfully and smoothly. This study is a longitudinal study with retrospective approach to determine the correlation between self-efficacy and the mark of OSCE to the third year students of Faculty of Medicine, University of Riau. The sample 102 students of this study were taken by total sampling technique. Primary data was taken by self-efficacy questionnaire modified from Rizkia research based on the theory of Bandura and secondary data from mark of the OSCE taken from manager skill lab. Statistical test to determine the correlation between self-efficacy and the mark of OSCE used Spearman test. The results of this study showed that there is no significant correlation between self-efficacy and the mark of OSCE (r=0.137; p=0.170). The conclusion of this study there was no correlation between self-efficacy and mark of the OSCE in the students third year of medical university riau.Keywords: self-efficacy, mark of the OSCE, medical students